1999
DOI: 10.1080/00071669987007
|View full text |Cite
|
Sign up to set email alerts
|

Tenderness, moisture loss and post-mortem metabolism of broiler Pectoralis muscle from electrically stimulated and air chilled carcases

Abstract: 1. This study was to evaluate the effects of post-mortem electrical stimulation (ES) on carcase moisture loss and on tenderness, R-value and pH of breast fillets following air chilling. 2. In each of 4 replications, 8 birds were electrically stimulated and 12 birds were controls. The ES birds were stimulated at the head in a 1% saline bath (450 V, 0.45 A, 2 s on/1 s off for 7 pulses). After evisceration the carcases were air chilled in a cooler at 1 to 2 degrees C with an average relative humidity of 91% and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…During water chilling, all carcasses gained weight resulting in a postchill carcass yield of 78.2% for soft-scalded and 76.1% for hard-scalded carcasses, a difference of 2.1% (P < 0.05). These data are in general agreement with other publications, in which immersion water-chilled broiler carcasses gained 4 to 12% of the prechill carcass weight and air-chilled carcasses lost up to 3% of their prechill weight with greater differences with longer chilling times (Fromm and Monroe 1958;Klose et al, 1960;Bigbee and Dawson, 1963;Sanders, 1969;Thomson et al, 1975;Hale and Stadelman, 1973;Thomson et al, 1984;Bilgili et al, 1991;Mielnik et al, 1999;Skarovsky and Sams 1999;Young and Smith, 2004;Jeong et al, 2011;Perumalla et al, 2011). Recently, Zhuang et al (2008) reported that airchilled carcasses lost 2.4% of their weight after 150 min of chilling, whereas immersion water-chilled carcasses gained 4.6% of their weight after 50 min, resulting in a difference of 7% between chilling methods.…”
Section: Resultssupporting
confidence: 93%
“…During water chilling, all carcasses gained weight resulting in a postchill carcass yield of 78.2% for soft-scalded and 76.1% for hard-scalded carcasses, a difference of 2.1% (P < 0.05). These data are in general agreement with other publications, in which immersion water-chilled broiler carcasses gained 4 to 12% of the prechill carcass weight and air-chilled carcasses lost up to 3% of their prechill weight with greater differences with longer chilling times (Fromm and Monroe 1958;Klose et al, 1960;Bigbee and Dawson, 1963;Sanders, 1969;Thomson et al, 1975;Hale and Stadelman, 1973;Thomson et al, 1984;Bilgili et al, 1991;Mielnik et al, 1999;Skarovsky and Sams 1999;Young and Smith, 2004;Jeong et al, 2011;Perumalla et al, 2011). Recently, Zhuang et al (2008) reported that airchilled carcasses lost 2.4% of their weight after 150 min of chilling, whereas immersion water-chilled carcasses gained 4.6% of their weight after 50 min, resulting in a difference of 7% between chilling methods.…”
Section: Resultssupporting
confidence: 93%
“…Much research has been conducted to study the factors influencing meat tenderness and water-holding capacity (Fletcher, 2002). Genetic stock and selection (Smith, 1963), age, sex, location (Castaneda et al, 2005), pre-and postslaughter chilling (Alvarado and Sams, 2000) and postmortem metabolism (Skarovsky and Sams, 1999) were factors affecting quality of muscle. About 88 to 95% of water in the muscle is held intracellularly within the space between actin and myosin filaments (Ranken, 1976;Offer and Knight, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that elevated temperatures or slower chilling rates may accelerate postmortem glycolysis and ultimate meat texture and functional properties [29,30,31,32,33,34,35,36,37]. Huezo et al [38] demonstrated that chilling method (air or immersion) had no effect on breast fillet tenderness when fillets are deboned 24 h postchill.…”
mentioning
confidence: 96%